Understanding depression - Nydegger, Rudy V., 1943- (Santa Barbara, California : Praeger an imprint of ABC-CLIO, LLC, 2016)
"Straightforward and easy to read yet thorough and accurate, this book provides a complete overview of depression that describes the historical background of clinical depression, the various types of mood disorders, and their impact on the health and well-being of people and society. Depression is a serious health issue that affects a greater proportion of people than many would suspect. A recent report by the World Health Organization stated that depression is the predominant cause of illness and disability for those age 10 to 19 worldwide, and more than 40 percent of U.S. college students reported experiencing symptoms of depression. Written by a clinical psychologist who has treated depressed patients and has also taught and done research in the clinical area for more than 40 years, this book presents the best and most current information that is available about depression that covers general background, theory, research results, and treatment methods in easy-to-understand, nontechnical language. The book discusses the various different types of mood disorders and what their impact is on the health and well-being of people and society. It helps readers to understand how those who are depressed suffer, what it feels like, and how their symptoms affect their daily lives. One chapter of the book is dedicated to answering a very common question regarding depression: "Who gets it, and why?" Many major and different types of depression are covered, including adjustment disorder with depressed mood, atypical depression, depressive personality dysthymic disorder, major depressive disorder, postpartum depression, premenstrual dysphoric disorder, seasonal affective disorder, and unipolar depression. The final chapter of the book draws conclusions based on the information presented, identifies effective treatments for depression, and suggests ways that individuals can cope with depression." -- Publisher's description
What is depression? -- Who can develop depression and what causes it? -- The different types and manifestations of depression -- Gender and depression -- Life cycle issues and depression -- Special groups and depression: race, ethnicity, and sexual orientation -- Treatment of depression: psychological therapies -- Treatment for depression: medical and alternative methods -- Pulling it all together: what do we know?
Includes bibliographical references and index.
Keywords: Depression, Mental; Depression, Mental -- Treatment